THE EFFECT OF INDONESIAN VELVET BEAN EXTRACT ON THE FERTILITY OF ALBINO MALE MICE - Sardjono, Ratnaningsih Eko; Pradipta, Viensa; Musthapa, Iqbal (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: This research aims to determine the dose of Indonesian velvet bean (Mucuna pruriens) extract which has significant effect on the ferlitity mice (concentration, motility and morphology of mice sperm). The extract is expected to become an alternative infertility herbal medicine relatively more secure and affordable replacing synthetic hormonal drugs which tend to have negative effects. Methods: The seed was taken from Yogyakarta Indonesia. Fertility test was done to fertile adult male albino mice 12 w old, weighing 25-35 grams. Fertility tests performed on seven groups of mice; i.e. negative control, positive control and treatment groups (five dose levels at 50, 100, 150, 200 and 250 mg/kg body weight). Subsequent fertility test results were statistically tested, including tests of normality (Kolmogorov-Sminov) followed by T test (Independent-Samples T Test). Results: The sperm concentration and motility increased as an increased dose of seed extract was applied, as well as decreased abnormal morphology. The highest change in the quality and quantity of sperm occurred at the dose of 250 mg/kg body weight with increased sperm concentration of about 22 million, sperm motility increased by 18% and decreased abnormal sperm morphology by 12%. Statistical analysis showed a significant increase in sperm concentration and motility at doses of 100, 150, 200 and 250 mg/kg body weight, whereas a significant decrease of abnormal sperm morphology was found at doses of 150, 200 and 250 mg/kg body weight. Conclusion: Based on this study it is concluded that Indonesian velvet beans seed extract can increased the fertility of albino male mice significantly at dose level 250 mg/kg body weight.